AL161431.1 is identified as a biomarker for bladder cancer progression and immunotherapy response - Sihao Zhang; Yaxuan Wang; Zhenwei Han; Baosai Lu; Kexin Sun; Zhihai Teng; Chenggen Jin; Fang Li; Hao Yuan; Fengran Guo; Yanping Zhang (Scientific Reports)
Abstract LncRNA AL161431.1 is currently known as a factor that can promote epithelial-mesenchymal transition. However, its role in the prognosis, immune infiltration and progression of bladder cancer (BLCA)patients is still unclear. The expression of AL161431.1 is elevated in BLCA tissues compared to normal tissues according to the TCGA database. By combining this data with clinical information, patients with high AL161431.1 expression have more advanced clinicopathological stages and shorter survival periods. Furthermore, AL161431.1 was identified as an independent prognostic factor for bladder cancer. We further analyzed the differences in immune infiltration, tumor mutation burden (TMB), immune checkpoints, and sensitivity to immunotherapy between groups with different levels of AL161431.1 expression. Enrichment analysis demonstrated that AL161431.1 is associated with numerous immune signaling pathways. High expression of AL161431.1 in cancer tissues was confirmed by qRT-PCR. CCK8, transwell, and wound healing demonstrated the oncogenic effects of AL161431.1. In conclusion, AL161431.1 is associated with immune infiltration in bladder cancer and has the potential to become a biomarker for predicting the prognosis of BLCA.